Dinamika dan Solusi Perlindungan Anak di Sekolah - Laurensius Arliman S (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2017)
Children as the nation's next generation, should be protected from childhood to adulthood. If the child since childhood was in the neighborhood crime, the boy can be the perpetrators of criminal acts in the future, and will be disturbing people's lives. It is wise if the protection of children starting in school. School as place a child studying, along with peers, and learn to respect for peers, with smaller or teachers. Nowadays, very sad child protection in the school environment, imagine in the school of environmental protection of children is not running properly, many child protection were violated, so kids do not feel comfortable at school, absences from school, or drop out of school. Against this it's good, we are all concerned with the protection of children, especially in the area of the school. This paper tries to offer the world the concept of the protection of children in schools on an ongoing basis, starting from the urgency of the protection of children in school, and the dynamics of child protection solutions in schools, as well as offering a sustainable concept of child protection in the school. The conclusion of this paper expects that all parties can participate in an ongoing child protection in the school. Keywords: Dynamic, Solution, Protection, Child, School Anak sebagai generasi penerus bangsa, harus dilindungi dari kecil sampai dewasa. Jika anak sejak kecil sudah berada di dalam lingkungan kejahatan, anak itu pasti menjadi pelaku tindak pidana di kemudian hari, dan akan meresahkan kehidupan masyarakat. Sangat bijak jika perlindungan anak dimulai di dunia sekolah. Sekolah sebagai tempat anak menimba ilmu, bergaul dengan teman sebaya, dan belajar menghargai kepada teman sebaya, teman yang lebih kecil ataupun para guru. Sekarang ini, perlindungan anak sangat menyedihkan di lingkungan sekolah, bayangkan di lingkugan sekolah perlindungan anak tidak berjalan dengan semestinya, banyak perlindungan anak yang dilanggar, sehingga anak tidak merasa nyaman di sekolah, absen dari sekolah, atau putus sekolah. Terhadap hal tersebut ada baiknya, kita semua memperhatikan perlindungan anak, terutama di wilayah sekolah. Tulisan ini mencoba menawarkan gagasan konsep perlindungan anak di dunia sekolah secara berkelanjutan, dimulai dari urgensi perlindungan anak di sekolah, dinamika dan solusi perlindungan anak di sekolah, serta menawarkan konsep perlindungan anak yang berkelanjutan di sekolah. Kesimpulan dari tulisan ini mengharapkan semua pihak dapat berpartisipasi di perlindungan anak yang berkelanjutan di wilayah sekolah. Kata Kunci: Dinamika, Solusi, Anak, Perlindungan, Sekolah